Pengaruh Model Pembelajaran Learning Cycle 7E Terhadap Kemampuan Menulis Teks Berita Siswa Kelas VIII MTs Nurul Falah Talagahurang Tahun Ajaran 2024/2025 - Holil, Holil (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2024)
The learning cycle 7E learning model is one of the learning models that allows students to optimize their way of thinking, searching, finding, and explaining the concepts that have been learned. This study aimed to determine the effect of learning models on the ability to write news texts in class VIII, students of MTs Nurul Falah Talagahurang school, the year 2024/2025. This research method uses a quantitative method of experimental type. Data analysis using one group design, and IBM SPSS Statistics T-test. Research results Based on the pretest value, an average value of 53.05 was obtained with a low category, and the posttest results after treatment were 72.90 with a good category. The results of the Paired Sample T-test hypothesis, got a Sig value, of 0'001 <0.05 which showed that there was a significant difference between the pretest and posttest results, then the results of the t-count value of 13.976> t-table 2.093 the t-count value is greater than the t-table so that the Ha hypothesis is accepted. Shows that there is an influence of the use of the learning cycle 7E learning model on the ability to write news texts for students.